Design And Characterization Of Chitosan Nanoparticles Of Felbinac Using Doe - Suresh Jadkar, Sagar; Kumar, Sunil (Journal of Neonatal Surgery, 2025)
The design and characterization of chitosan nanoparticles loaded with felbinac have been optimized using a Design of Experiments (DOE) approach to improve the drug's therapeutic performance. Felbinac, a nonsteroidal anti-inflammatory drug (NSAID), suffers from poor bioavailability and limited therapeutic efficacy when administered conventionally. Chitosan nanoparticles offer an innovative solution for enhancing solubility, controlled release, and targeted delivery. In this study, various formulations of felbinac-loaded chitosan nanoparticles were prepared and characterized for key parameters, including percentage yield, entrapment efficiency, particle size, and drug release profile. Response surface plots and contour plots were employed to determine the optimal formulation parameters. The formulations exhibited significant variations in entrapment efficiency (63.25%–79.98%) and particle size (75.65–132.87 nm). The optimized formulation (F14) showed excellent drug entrapment efficiency (78.85%) and a small particle size (75.65 nm). The in vitro release studies demonstrated a controlled release profile, with 93.32% of the drug released after 24 hours. The drug release kinetics followed a diffusion-controlled mechanism, as indicated by the Korsmeyer-Peppas model (R² = 0.9836). The findings suggest that chitosan nanoparticles can effectively enhance the bioavailability of felbinac and provide a controlled-release system for sustained therapeutic effects.